2017
DOI: 10.1111/coa.12849
|View full text |Cite
|
Sign up to set email alerts
|

Coblation® intracapsular tonsillectomy (tonsillotomy) in children: A prospective study of 500 consecutive cases with long‐term follow‐up

Abstract: Our experience of this technique has been very positive, with excellent control of both obstructive and infective symptoms, and exceptionally low rates of complications. Further work will be required to allow conclusive demonstration of its advantages over extracapsular tonsillectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 11 publications
1
50
0
1
Order By: Relevance
“…Systematic reviews in 2012 and 2015 showed significant improvements in time to return to normal diet and reduction in postoperative readmissions for dehydration and bleeding . The disadvantages are the risk of symptomatic tonsil regrowth (rates between 2 and 13%) and recurrent tonsillitis, both of which may lead to the need for revision surgery.…”
Section: What Does a Tonsillectomy Involve?mentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic reviews in 2012 and 2015 showed significant improvements in time to return to normal diet and reduction in postoperative readmissions for dehydration and bleeding . The disadvantages are the risk of symptomatic tonsil regrowth (rates between 2 and 13%) and recurrent tonsillitis, both of which may lead to the need for revision surgery.…”
Section: What Does a Tonsillectomy Involve?mentioning
confidence: 99%
“…Tonsil capsule preserved, with variable amount of denatured tonsil tissue remaining, and no exposed pharyngeal muscle …”
Section: What Does a Tonsillectomy Involve?mentioning
confidence: 99%
“…18 A 'long-term prospective study' on 500 paediatric patients undergoing coblation subtotal tonsil reduction tonsillotomy revealed only 2.4% underwent revision tonsil surgery but on closer examination, the mean follow-up was only 7.4 months. 23 While our study was not designed to identify tonsil regrowth or the need for revision surgery, the use of an electronic medical record allows us to look beyond the cut-off period utilized for our primary goals. As of May 2020, an identical figure of 2.4% (n = 8) of our subtotal tonsil reduction cohort have undergone completion tonsillectomy, all for recurrent tonsillitis in the tonsil remnant.…”
Section: Discussionmentioning
confidence: 99%
“…Si se utilizan elementos generadores de calor como el cauterio monopolar, se produce una agresión tisular con la corriente generada de aproximadamente 400 a 600 °C que prolonga bastante el tiempo de cicatrización. Cuando se utiliza la radiofrecuencia, la temperatura es ostensiblemente menor en un rango de 40-50 °C, lo que provoca una menor lesión y, por ende, una recuperación más temprana (5).…”
Section: Introductionunclassified